2019
DOI: 10.1002/pld3.169
|View full text |Cite
|
Sign up to set email alerts
|

The chloroplast and mitochondrial C‐to‐U RNA editing in Arabidopsis thaliana shows signals of adaptation

Abstract: C‐to‐U RNA editing is the conversion from cytidine to uridine at RNA level. In plants, the genes undergo C‐to‐U RNA modification are mainly chloroplast and mitochondrial genes. Case studies have identified the roles of C‐to‐U editing in various biological processes, but the functional consequence of the majority of C‐to‐U editing events is still undiscovered. We retrieved the deep sequenced transcriptome data in roots and shoots of Arabidopsis thaliana and profiled their C‐to‐U RNA edito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Therefore, the altered editing of the rpoB -467 site was not the cause of the phenotype of las1 . The chloroplast and mitochondria RNA editing events may be an indication of evolutionary adaptation (Chu and Wei, 2019 ). The rpl2 , rpoB and atpA gene sequences of the chloroplast genomes of different species were analyzed from the perspective of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the altered editing of the rpoB -467 site was not the cause of the phenotype of las1 . The chloroplast and mitochondria RNA editing events may be an indication of evolutionary adaptation (Chu and Wei, 2019 ). The rpl2 , rpoB and atpA gene sequences of the chloroplast genomes of different species were analyzed from the perspective of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the nonsynonymous or nonsense mutations are overall deleterious and while the synonymous mutations are regarded as neutral. Usually, the nonsynonymous to synonymous ratios are measurements for the adaptiveness of different sets of nonsynonymous mutations [20,21]. Accordingly, we observed that the fixed to polymorphic ratios of nonsynonymous or nonsense mutations are significantly lower than that of synonymous mutations (Fig.…”
Section: Fixed To Polymorphic Ratios Reveal the Weak Selection On Synmentioning
confidence: 67%
“…Editing at these sites resulted in nonsynonymous amino acid substitutions ( Figure S2A ), which are highly conserved among different species as indicated by the result of multiple alignment ( Figure S2B ). Compared with synonymous editing sites, nonsynonymous editing sites commonly showed higher conservation levels as well as editing levels [ 30 , 38 ], and nonsynonymous sites are more essential and functional, suggesting that detection of novel C-to-U editing sites in this study will provide valuable source for rice biological study.…”
Section: Resultsmentioning
confidence: 99%